Talent acquisition and retention policies for generation Z in family business - Esteve Seguí, Guillem (2025)
In today’s business environment, talent management has become a crucial discipline for achieving sustainable competitive advantage. This study focuses on the talent acquisition and retention policies of Generation Z in Spanish family businesses, a significant sector in the country’s economy. Using a mixed approach of qualitative interviews and quantitative surveys, it explores the perceptions of managers and young employees on talent management policies. The results reveal that although many companies implement effective practices, there are significant differences in adapting to generational change. Factors such as fluid communication, continuous training and the inclusion of employees in strategic decision-making are key to the retention of young talent. In addition, job flexibility and a work environment that reflects the values of Generation Z are essential. This study contributes to both the theory and practice of human resource management, providing recommendations for improving the retention and satisfaction of young employees. Practical implications include the need for regular policy audits, the development of mentoring programs, and the implementation of regular satisfaction surveys to align with employee expectations.